Hemodynamic Disturbances in Posterior Circulation Stroke: 4D Flow Magnetic Resonance Imaging Added to Computed Tomography Angiography - Malm, Jan; Birnefeld, Johan; Zarrinkoob, Laleh; Wåhlin, Anders; Eklund, Anders (Frontiers in Neuroscience, 2021)
Objective. A clinically feasible method to quantify blood flow, hemodynamics and collateral flow in the vertebrobasilar arterial tree is missing. In this prospective study, the prospect of quantifying blood flow and its direction using 4D flow MRI in patients with posterior circulation infarcts was evaluated. Flow patterns indicating hemodynamic disturbances and a compromised flow were examined in relation to findings revealed on computed tomography angiography (CTA) and diffusion weighted MRI (DWI). Methods. Twenty-five patients with acute brain infarct in the posterior circulation were investigated. At onset, all patients were examined with CTA followed by MRI (4D flow MRI and DWI). Patients were divided into proximal/middle (n=16) and distal territory infarcts (n=9). Flow rates (mL/min) were calculated for internal carotid- (ICA), vertebral- (VA), basilar- (BA), posterior cerebral- (P1 and P2) and the posterior communicating arteries (Pcom). In a control group of elderly, the 90th and 10th percentiles of flow were calculated to define any pathological blood flow in each artery. Results. Using 4D flow MRI, flow disturbances could be detected in individual arteries, for example hypo- or hyperflow, reversed flow or compensatory collateral flows. Interpreting these flow disturbances, together with CTA, made it possible to identify groups with distinct flow patterns, specifically those with pronounced hemodynamic disturbance. Proximal/middle territory stenoses and occlusions were characterized by a low inflow of blood through the VA and BA, counterbalanced by increased inflow via the Pcom. Distal territory infarcts were also accompanied by a decreased VA inflow, despite lack of any VA obstruction, and did not have a compensatory increased inflow via the Pcom. An overall impression was that a normal CTA nearly always revealed a normal blood flow distribution. Conclusion. 4D flow MRI supplements CTA by adding information about the severity of arterial hemodynamic impairment in the posterior circulation. We were for the first time able to quantify the ability of the posterior communicating artery to secure blood flow to the posterior circulation in patients with impaired vertebrobasilar inflow. 4D flowMRI has potential to contribute to the planning for subacute medical, surgical or endovascular treatments, and to improve prognostic predictions in posterior circulation stroke.